Improved Entrepreneurial Performance of Ginger Processor Based on Local Wisdom's Potential - Nurliani Nurliani; Rasmeidah Rasyid; Ida Rosada; A. Ralle (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2022)
This investigation was conducted for six months in Mallawa District, Maros Regency, South Sulawesi Province. Using questionnaires to apply the case study method to the business of processing ginger into beverages. Sample stability by use of targeted sampling. The study of data employs descriptive analysis with cross-tabulation and percentages, value-added analysis based on the Hayami Method, and correlation analysis. Results indicated that the values of local knowledge that shape the entrepreneurial spirit of ginger processing in Mallawa District, Maros Regency are honesty, self-confidence, courage to take risks, never giving up, innovative thinking, persistence, patience, hard effort, and teamwork. The entrepreneurial behavior of ginger processors demonstrates that the entrepreneur's cognitive behavior is fairly good, his affective behavior is good, and his psychomotor behavior is excellent. The association between entrepreneurial activity and corporate performance is significant. Processing raw ginger into